Spectral Characteristics of High-Yielding Varieties of Rice Plants Using Landsat 8 Data - Dewi, Candra; Supianto, Ahmad Afif; Sutrisno, Sutrisno (AGRIVITA, Journal of Agricultural Science, 2013)
In applying remote sensing technology for inventory, evaluation and estimation of rice crop production, required the data of spectral characteristics changing of the plants during its growth phase. By identifying spectral characteristics, it will be recognized the objects in the images. This study identifies the spectral characteristics of high-yielding varieties of rice plants during their growth in Malang regency. Based on the results of field survey, the high yielding varieties that are commonly planted consist of IR64, Ciherang and Membramo. Then, from the identification of vegetation index is known that all these three varieties have different growth patterns, where the most distinct pattern found in IR64.